Nutritional Value of Amaranth - Waisundara, Viduranga Y. (IntechOpen, 2020)
Pseudocereals, belonging to the genus Amaranthus, have been cultivated for their grains for 8,000 years or more. The grain was a staple food of the Aztecs and was also considered an integral part of Aztec religious ceremonies. The book primarily focuses on the nutrient properties of amaranth and expresses its viewpoint in considering this crop as a remedy for many nutrient deficiencies and curbing food insecurity. The functional properties of the grain are immense and it is clear that the crop would be a valuable agricultural product around the world.